Computer and Internet use at work in 2001. - Hipple, Steven; Kosanovich, Karen (Monthly Labor Review, 2003)
An analysis of computer and Internet use at work in 2001, including statistics by occupation and industry; by sex, race, and educational attainment; and on job search activity using the Internet.